Tumor immune microenvironment heterogeneity at the invasion front and tumor center in oral squamous cell carcinoma as a perspective of managing this cancer entity - Mamilos, Andreas; Lein, Alexander; Winter, Lina; Ettl, Tobias; Künzel, Julian; Reichert, Torsten E.; Spanier, Gerrit; Brochhausen, Christoph (Journal of Clinical Medicine, 2023)
Background: Evaluating the tumor microenvironment and its influence on clinical management and therapy response is becoming increasingly important. However, only a few studies deal with the spatial distribution of immune cells within the tumor. This study aimed to describe the topology of immune cells in the microenvironment of oral squamous cell carcinoma (OSCC) sectioned by tumor invasion front and tumor center and to test their prognostic relevance regarding patient survival. Methods: A total of 55 OSCC patient specimens were collected retrospectively. The cancer tissue was immunohistochemically stained using an automated tissue stainer Ventana Benchmark Ultra (Roche) and analyzed using discrete expression marker profiles on immune cells. We investigated CD4+ lymphocytes, CD8+ lymphocytes, CD68+ macrophages, CD163+ macrophages, and M1 macrophages regarding their spatial distribution. Results: The statistical analysis revealed that the quantity and distribution of CD4+ (p = 0.007), CD8+ (p < 0.001), CD68+ (p < 0.001), CD163+ cells (p = 0.004), and M1 (p < 0.001) macrophages were significantly higher at the invasion front compared to the tumor center in all observed cases. However, high and low immune cell counts in the tumor center and invasion front were not associated with overall survival. Conclusion: Our results show two distinct immune microenvironments of the tumor center compared to the invasion front. Future studies are needed to explore how these results can be leveraged to improve patient therapy and outcome.